Marketing Strategy In Developing Smes Products Through Social Media (Case Study Of Smes At Sumsel – Babel, Indonesia) - Enos Julvitra; Meilaty Finthariasari; Arfan Ikhsan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to develop social media-based SME products in the South Sumatra-Babel region. This type of research is descriptive with a qualitative approach to objectively analyze the situation regarding strategies in developing SMEs products in South Sumatra - Babel, Indonesia. The informants of this study were SME business owners and their employees, accompanied by direct observation in the field. Based on the results of the SWOT analysis of marketing strategies that can be seen in table 4.2, internal conditions have a total strength with a total score of 12 which shows greater strength than weakness with a total score of 0. While external has a total opportunity with a total score of 7 where the opportunity is greater than the threat which has a total score of 4. This shows that SMEs in South Sumatra - Babel have strong internal conditions and external opportunities.